2013
DOI: 10.1080/10550887.2013.824331
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Focus and Experiences of Smartphone Applications for Addiction Recovery

Abstract: Addiction recovery Smartphone applications (apps) (n = 87) identified on the Google Play store in 2012 were coded, along with app user reviews, to explore functions, foci, and user experiences. Content analysis revealed that apps typically provided information on recovery, as well as content to enhance motivation, promote social support and tools to monitor progress. App users commented that the apps helped to inform them, keep them focussed, inspire them, and connect them with other people and groups. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 16 publications
4
60
0
3
Order By: Relevance
“…The use of mobile platforms for delivery of self-help interventions specifically in the field of mental health has also seen phenomenal growth across the globe in the last few years; though several of them are yet to be formally evaluated (Huguet et al, 2016;Savic et al, 2013). Although the utility of mobile apps in resource-scarce settings is being recognized; the need for determining consistent ways of evaluating performance of mental health apps has also been emphasized (Powell et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…The use of mobile platforms for delivery of self-help interventions specifically in the field of mental health has also seen phenomenal growth across the globe in the last few years; though several of them are yet to be formally evaluated (Huguet et al, 2016;Savic et al, 2013). Although the utility of mobile apps in resource-scarce settings is being recognized; the need for determining consistent ways of evaluating performance of mental health apps has also been emphasized (Powell et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…A literature review of interventions for substance-abusing populations utilizing telemedicine revealed that participants were supportive of technology, and identified the need for more research in this field (Young, 2012). In addition, an analysis of addiction recovery Smartphone applications revealed that users found them helpful for accessing both information and social support, however, more research is needed (Savic, Best, Rodda, & Lubman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even within the context of crystal methamphetamine apps that do provide high quality and evidence-based information, the lack of interactive and engaging features represents a significant lost opportunity for reach and impact [31]. Only three apps offered interactive features such as monitoring, tracking or goal-setting.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…We identified several reviews of apps that target alcohol use and related behaviours e.g. [28][29][30], or addiction and addictive behaviours in general [31]. We found one review that specifically reviewed apps that promote illicit drug use [32], and one review that analysed illicit drug overdose apps [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation